2001
DOI: 10.1063/1.1402158
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear optical properties of chalcogenide glasses: Observation of multiphoton absorption

Abstract: We report observation of four- and five-photon absorption in the chalcogenide glasses at the telecommunication wavelengths. The nonlinear refractive index is sufficiently large that the optical switching criterion is satisfied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(61 citation statements)
references
References 8 publications
3
55
0
1
Order By: Relevance
“…1(a), the best fits result in a 3PA coefficient of 0.016 cm 3 /GW 2 for the ZnO crystal. It has been pointed out that 3PA Z scans are considerably different from 2PA Z-scans [24]. Our results in Fig.…”
Section: Z-scan Theories On Multiphoton Absorberssupporting
confidence: 77%
“…1(a), the best fits result in a 3PA coefficient of 0.016 cm 3 /GW 2 for the ZnO crystal. It has been pointed out that 3PA Z scans are considerably different from 2PA Z-scans [24]. Our results in Fig.…”
Section: Z-scan Theories On Multiphoton Absorberssupporting
confidence: 77%
“…We have found wavelength-dependent measurements of the nonlinear index, n 2 , for arsenic sulfide from different data sources [150,[165][166][167][168][169][170][171][172][173][174]. As shown in Figure 3, although slightly scattered, these n 2 values in arsenic sulfide are as high as those in silicon and would not be strongly wavelength-dependent beyond 1.55 µm, because it is longer than the half-bandgap wavelength.…”
Section: Methodsmentioning
confidence: 87%
“…For example, As 2 S 3 and As 2 Se 3 have bandgap energies around 2.26 eV [150,151] and 1.77 eV [152], and they are transparent up to 12 and 15 µm [153], respectively. Although in this paper chalcogenide glasses are not considered a material for the core of a waveguide, one may use them for waveguide cladding and slot layer [53,58].…”
Section: Methodsmentioning
confidence: 99%
“…Many reports indicate that a two-photon absorption process is responsible for the optical nonlinearities observed in chalcogenide glasses. Recently, however, a multiphoton absorption process has been suggested for the nonlinearities observed in these glasses [29]. It was found that for 1.55 µm radiation, the ratios of band gap energy to photon energy are 2.8, 3.4, and 4.3 for As 2 S 3 -, GeS 2 -and TeO 2 -based samples, respectively.…”
Section: Nonlinear Optical Analysismentioning
confidence: 99%